2014
DOI: 10.1111/ppa.12310
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of infection and colonization of Quercus ilex fine roots by Phytophthora cinnamomi

Abstract: Quercus ilex is one of the European forest species most susceptible to root rot caused by the oomycete Phytophthora cinnamomi. This disease contributes to holm oak decline, a particularly serious problem in the 'dehesas' ecosystem of the southwestern Iberian Peninsula. This work describes the host-pathogen interaction of Q. ilex and P. cinnamomi, using new infection indices at the tissue level. Fine roots of 6-month-old saplings inoculated with P. cinnamomi were examined by light microscopy and a random pool o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 29 publications
5
22
0
1
Order By: Relevance
“…9 inoculation method interaction reported by Haque and Diez (2012). Using the dip method with a suspension of P. cinnamomi chlamydospores, at 3 dpi all tissues of secondary Q. ilex roots were colonized, but first aerial symptoms consisted of leaf discolouration by 14 dpi (Ruiz Gómez et al 2015). Root dip into a zoospore suspension mimics the process that occurs in nature, probably better than the mycelium-root contact method.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…9 inoculation method interaction reported by Haque and Diez (2012). Using the dip method with a suspension of P. cinnamomi chlamydospores, at 3 dpi all tissues of secondary Q. ilex roots were colonized, but first aerial symptoms consisted of leaf discolouration by 14 dpi (Ruiz Gómez et al 2015). Root dip into a zoospore suspension mimics the process that occurs in nature, probably better than the mycelium-root contact method.…”
Section: Discussionmentioning
confidence: 96%
“…The presence of haustoria, i.e. structures involving feeding relationships between the host and the pathogen (Judelson and Blanco 2005), and the formation of numerous chlamydospores indicate that P. cinnamomi may temporarily behave as a biotrophic pathogen (Crone et al 2013a;Ruiz Gómez et al 2015). It was recently postulated that a necrotrophic mode of P. cinnamomi growth would not provide enough nutrients to produce the large numbers of chlamydospores (Crone et al 2013a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous cytohistological observations have shown that P. cinnamomi colonizes Q. suber and Q. ilex penetrating to the phloem and xylem vessels and leading to occlusion, at least in 2-to 6-month-old plants (Pires et al 2008;Horta et al 2010;Medeira et al 2012a;Ruiz-Gómez et al 2014). In addition, recent cytological and physiological studies showed that cryptogein (elicitin secreted by Phytophthora cryptogea) and capsicein (secreted by Phytophthora capsici) induced a resistance response on cork oak against infection by P. cinnamomi (Medeira et al 2012a) and that α-CIN has the same effect in Castanea sativa (Medeira et al 2012b).…”
Section: Discussionmentioning
confidence: 99%